Caribbean Achievement in Britain Psychosocial Resources and Lived Experiences - E. Maduro, Winniey (Springer International Publishing, 2018)
This book explores a range of psychosocial resources, and discusses them in relation to lived experiences and outcomes in educational and socioeconomic domains. It offers close insights into the complex relationship between psychosocial resources, such as familial influence, religiosity, aspirations, and socioeconomic progression in Britain. This is achieved by exploring the lived experiences of a sample group of Caribbeans, one of Britain's most internally diverse but discernibly disadvantaged social groups. Detailed accounts of the participants' experiences are offered to provide insights to a wide range of stakeholders in education. Teachers, behaviour specialists, parents, policy advocates, psychologists, social researchers, social justice warriors and lay people will all benefit from this empirically informed perspective on psychosocial resources and their implications for educational attainment and socioeconomic progress. The book implores the reader to appreciate more fully how psychosocial resources play out in outcomes of achievement and progression, and how such outcomes may be improved among members of some disadvantaged social groups. It will be an invaluable resource for students, researchers, and educators in the fields of Education, Sociology, and Psychology.